A Hybrid Transmission Based Data Collection Scheme With Delay and Reliability Guaranteed for Lossy WSNs - Jinhuan Zhang; Peng Hu; Jun Long (IEEE Access, 2019)
Mobile computing provides new ways of data collection on the Internet of Things (IoT). The sensed environment information by various sensing devices could make access to a wireless sensor network (WSN) through access points and vice versa. Improving the energy efficiency for a prolonged network lifetime while meeting the adaptive performance requirements under the guarantees of transport delay and reliability is an important problem to be solved in data collection for lossy and large-scale wireless sensor networks (WSN). Although many previous studies devoted to improving the energy efficiency, reliability, or network delay, they mainly focus on one of the performance metrics of the WSN. In this paper, a hybrid transmission scheme integrating the packet reproduction (PR) and Hop-by-Hop Automatic Repeat-reQuest (HBH ARQ) schemes are proposed to improve energy efficiency and reduce delay under guarantee of reliability for the lossy WSN. In the proposed scheme, the network is divided into two parts by a hybrid boundary where the location information is used to help determine the routing changes between the PR and HBH ARQ schemes. Some key parameters involved in the scheme are discussed and analyzed. The effectiveness of the proposed scheme is evaluated via extensive simulation results.